(untitled) (Journal of Bio-Science, 2016)
Context: The distribution of different size groups of litter invertebrates in varying gradations of moisture conditions is therefore of interest for a better understanding of the coordination of the components of the ecological community. Objectives: The aim of this work is to evaluate the effect of long-term average moisture conditions on the basic characteristics of the litter macrofauna of plantations in southern Ukraine. Materials and Methods: Invertebrates were collected with pitfall traps annually throughout the vegetational seasons of 20012013 in 176 plantation sites. Results: The average number and the quantity of invertebrate species in the litter decreases with the increase of the moisture content. The indices of biological diversity are maximal in xeromesophilous and mesophilous moisture conditions. Phytophages are distributed evenly in the litter of forest plantations. The number of saprophages is maximal in xeromesophilous (36%) and minimal in hygromesophilous (3%) conditions. Zoophages increase in relative abundance from 14% in mesoxerophilous to 63% in hygromesophilous conditions. The abundance of polyphages does not change significantly in varying gradations of moisture (2646%). The size structure of communities is dominated by the group ranging from 4 to 7 mm in body length (3152%). The relative abundance of the size group exceeding 20 mm in body length reaches its maximum (16%) in mesoxerophilous conditions, and decreases (410%) in other gradations of moisture. The share of the size group of <4 mm is maximal (28%) in mesophilous conditions. Carabidae, Formicidae and Lycosidae form part of the dominant families in all four of the moisture gradations of artificial forests studied, while other families represent more than 3% only in plantations belonging to three gradations of moisture. Conclusion: Litter moisture is a limiting factor for invertebrate existence in the extreme conditions of forest ecosystems, especially in the south of the steppe zone of Ukraine. J. bio-sci. 22: 77-88, 2014